Smart Tracking Design In Finding Solar Power Plants - Suwarno Suwarno; Rohana Rohana; Darma Yulianti Purba (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
We know that solar heat can be used as one of the natural resources that are still very abundant on earth and can be used as a new source of energy or better known as solar cells and power plants that use solar cells are generally still static. Therefore we need a mechanical system that can move the position of the solar panel so that it can move according to the position expected by the use of solar panels to get energy from the sun. Arduino Uno serves as the control center of all systems built and tools. in moving the solar panel using Askremote control to give orders to the L298 module as a controller of the dc motor so that the dc motor can move according to the design and construction of the system embedded into the Arduino and the Photo Interrupter functions as a barrier to the movement of the dc motor.